Unsymmetrical cyanine dye via in vivo hitchhiking endogenous albumin affords high-performance NIR-II/photoacoustic imaging and photothermal therapy - Pengfei Xu; Linan Hu; Cheng Yu; Weidong Yang; Fei Kang; Mingru Zhang; Pei Jiang; Jing Wang (Journal of Nanobiotechnology, 2021)
Abstract Herein, an unprecedented synergistic strategy for the development of high-performance NIR-II fluorophore is proposed and validated. Based on an unsymmetrical cyanine dye design strategy, the NIR-II emissive dye NIC was successfully developed by replacing only one of the indoline donors of symmetrical cyanine dye ICG with a fully conjugated benz[c,d]indole donor. This minor structural change maximally maintains the high extinction coefficient advantage of cyanine dyes. NIC-ER with endogenous albumin-hitchhiking capability was constructed to further enhance its in vivo fluorescence brightness. In the presence of HSA (Human serum albumin), NIC-ER spontaneously resides in the albumin pocket, and a brilliant ~89-fold increase in fluorescence was observed. Due to its high molar absorptivity and moderate quantum yield, NIC-ER in HSA exhibits bright NIR-II emission with high photostability and significant Stokes shift (>110 nm). Moreover, NIC-ER was successfully employed for tumor-targeted NIR-II/PA imaging and efficient photothermal tumor elimination. Overall, our strategy may open up a new avenue for designing and constructing high-performance NIR-II fluorophores.